2009
DOI: 10.14236/jhi.v17i1.709
|View full text |Cite
|
Sign up to set email alerts
|

Imminent adopters of electronic health records in ambulatory care

Abstract: Background Although evidence suggests electronic health records (EHRs) can improve quality and efficiency, provider adoption rates in the US ambulatory setting are relatively low. Prior studies have identified factors correlated with EHR use, but less is known about characteristics of physicians on the verge of adoption. Objective To compare characteristics of physicians who are imminent adopters of EHRs with EHR users and non-users. Design and participants A survey was mailed (June -November 2005) to a strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Recent studies have shown low adoption rates for HIT and have emphasised the important impact of these technologies on patient outcomes. [79][80][81] Similar to our study, Kaushal et al found that physician characteristics and financial status were barriers to HIT adoption.…”
Section: Comparison With the Literaturesupporting
confidence: 88%
“…Recent studies have shown low adoption rates for HIT and have emphasised the important impact of these technologies on patient outcomes. [79][80][81] Similar to our study, Kaushal et al found that physician characteristics and financial status were barriers to HIT adoption.…”
Section: Comparison With the Literaturesupporting
confidence: 88%
“…Kaushal et al administered a survey to populations of physicians to compare characteristics of those who use EHRs, those who do not, and those who plan to adopt EHRs within 12 months ('imminent adopters'). 22 They found imminent adopters were more experienced in the use of technology, a construct similar to finesse. Other investigators have used an a priori framework to assess physicians' expectations, demands, acceptability, experience and knowledge of computer-based consultation systems.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] A few studies investigate attitudes toward EHR adoption in inpatient 19 and academic ambulatory care settings. 20 Some have investigated adoption readiness using statewide survey samples of medical practices, [21][22][23][24] others have assessed physicians' perceptions of quality of care. 25 We know of no reports describing the attitudes and behaviours that predict EHR adoption, specifically e-prescribing adoption, in the primary care setting of an independent medical group.…”
Section: Introductionmentioning
confidence: 99%
“…To accomplish this, the ambulatory care side of the process may need to become proactive by implementing systems for obtaining the information they require. With the expansion of EMR implementations in ambulatory care, 23,[30][31][32] it is possible to assemble the components required to support more rapid and complete flow of information during discharges of patients. Like the medical group in which this intervention was implemented, many provider groups with EMRs already use interface engines to allow direct receipt of ADT and ORU messages and are using these in some applications.…”
Section: Discussionmentioning
confidence: 99%